Pengeluaran dan sumbangan sektor koko kepada pendapatan pekebun kecil di Malaysia : suatu analisis kecekapan - Wan Roshidah, Fadzim (2016)
The rapid development of cocoa downstream activities in Malaysia has strengthened cocoa demand and provides opportunities for cocoa farmers to increase their income. However, cocoa farmers appear to have not fully exploited the available market opportunities which resulted in an imbalance between the production and the grinding sectors. The decline in cocoa production is often associated with a reduction in acreage, but this is found not to be the main cause. Thus, this study attempts to unravel this problem by studying it from the aspect of production efficiency among cocoa farmers. In particular, the main objective of this study is to investigate the level of production efficiency, the factors that affect efficiency and the effect of efficiency on the income of farmers. For that purpose, this study uses a non-parametric approach (Data Enveloping Analysis) to a variable return to measure the efficiency of each cocoa farmer, the Tobit Model to identify the factors that drive production efficiency, and the Ordinary Least Square (OLS) model to analyze the effect of efficiency on the income of farmers. This study gathers a micro data set to get detailed information of cocoa smallholders. The results of the analyses show that the level of production efficiency among cocoa farmers in Malaysia is still at a low level at 0.576, which is caused by a number of factors that affect their income. Therefore, there is a need for an improvement and this study have identified that the driving factors to achieve maximum production are labour, numbers of clone, record keeping, the level of knowledge. the status of farm operators and location. Further, the study found that efficiency produces a positive impact on income of cocoa farmers in Malaysia.